On positionalities in research with international students - Spangler, Vera (Journal of International Students, 2023)
In this paper, I argue that if we want to further strengthen the current direction towards more innovative and critical methodological research designs in research with international students, we must engage more deeply and meaningfully with our own positionalities as researchers. In order to build a more accurate portrayal of our participants – international students, we must begin to acknowledge the dynamic multiplicity and situational understandings of positionalities and move away from monolithic and ascriptive presentation statements (e.g., nationality, age, gender). A critical appreciation of positionality helps us to develop a reflexivity that enhances the methodological strength of our research approaches and, considering the lack of nuance in many conceptions of international students, generate empirical material with international students that (more) faithfully represent their experiences and worlds. This, hopefully, allows us to counter inequalities in practice and move away from positions of deficit and problematic discourses and assumptions.